1991
DOI: 10.1111/j.1600-079x.1991.tb00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin N‐acetyltransferase activity in chicken retina: In vivo effects of phosphodiesterase inhibitors, forskolin, and drugs affecting dopamine receptors

Abstract: A role of D2-dopaminergic neurotransmission in the regulation of melatonin biosynthesis in retina was studied in vivo in chickens. The nighttime rise in serotonin N-acetyltransferase (NAT)--the penultimate and key regulatory melatonin-synthesizing enzyme--was potently inhibited by both acute light exposure and agonists of dopamine D2-receptor (quinpirole, bromocriptine, and apomorphine). Spiroperidol, a selective dopamine D2-receptor blocker, increased the enzyme activity in light-exposed chickens, but had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The D2 type of dopamine receptors appears to mediate this dopamine action, because only selective D, agonists (e.g., quinpirole, bromo-criptine) and D, blockers (e.g., spiroperidol) mimic and antagonize, respectively, the amine effect (Iuvone, 1986;Nowak and Zurawska, 19896;Zawilska and Iuvone, 1989;Nowak et al, 1990; see also Schorderet and Nowak, 1990). An important role of endogenous dopamine in a tonic suppression of the process of NAT induction in light-exposed retina is indicated by two facts: (1) spiroperidol, both in vitro (the frog eye cup preparation; Iuvone et al, 1987) and in vivo (chicken; the drug was given at different time points throughout the entire day under constant illumination; Zawilska et al, 1991; also present data) significantly enhanced the retinal NAT activity, most probably by blocking the photoreceptor membrane-localized D, receptors, and thus eliminating an inhibitory dopaminergic input to photoreceptors; (2) the administration to lightexposed chicks of aMpT, an effective in vivo inhibitor of dopamine synthesis at the step of tyrosine hydroxylation, dramatically decreased the retinal levels of dopamine and DOPAC (unpublished data) and, simultaneously, increased the activity of NAT (present data; see also Zawilska et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D2 type of dopamine receptors appears to mediate this dopamine action, because only selective D, agonists (e.g., quinpirole, bromo-criptine) and D, blockers (e.g., spiroperidol) mimic and antagonize, respectively, the amine effect (Iuvone, 1986;Nowak and Zurawska, 19896;Zawilska and Iuvone, 1989;Nowak et al, 1990; see also Schorderet and Nowak, 1990). An important role of endogenous dopamine in a tonic suppression of the process of NAT induction in light-exposed retina is indicated by two facts: (1) spiroperidol, both in vitro (the frog eye cup preparation; Iuvone et al, 1987) and in vivo (chicken; the drug was given at different time points throughout the entire day under constant illumination; Zawilska et al, 1991; also present data) significantly enhanced the retinal NAT activity, most probably by blocking the photoreceptor membrane-localized D, receptors, and thus eliminating an inhibitory dopaminergic input to photoreceptors; (2) the administration to lightexposed chicks of aMpT, an effective in vivo inhibitor of dopamine synthesis at the step of tyrosine hydroxylation, dramatically decreased the retinal levels of dopamine and DOPAC (unpublished data) and, simultaneously, increased the activity of NAT (present data; see also Zawilska et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether melatonin affects the retinal "dopaminergic activity" in vivo we have studied in retinas of light-exposed chicks the action of melatonin administered either peripherally or intraocularly on (1) dopamine metabolism, which during the light penod is high, and (2) NAT activity, which in animals kept under constant lighting conditions seems to be tonically inhibited by endogenously released dopamine (Zawilska et al, 1991).…”
mentioning
confidence: 99%
“…N = 12-22/ group biochemical and physiological studies have demonstrated that the effects of dopamine within the retina result from its interaction with two basic types of receptor that have been classified as D1 and D2 (Kebabian and Calne, 1979;Schorderet and Nowak, 1990). In line with this classification, it has been postulated that stimulation by dopamine of the D2-receptor is partially responsible for the light-induced suppression of the nocturnal increase in retinal NAT activity and melatonin level (Iuvone et al, 1987;Nowak and 2;urawska, 1989 b;Zawilska et al, 1991;. However, results of our recent experiments, performed with a number of dopamine receptors' selective ligands, suggested that at least in the retina of chick this effect of dopamine is mediated by a receptor with pharmacological characteristics fitting more the characteristics of the newly described D4-receptor than that of a "traditional" D2-receptor (present data; Nowak and Zawilska, 1994;Nowak, 1993, 1994a, b).…”
Section: Discussionmentioning
confidence: 93%
“…In several species, including frog, chicken, rat, mouse, cat and rabbit, exposure to light increases dopamine synthesis, release and metabolism in the retina (e.g., Da Prada, 1977;Iuvone et al, 1978;Parkinson and Rando, 1983 a, b;Nowak, 1988;Godley and Wurtman, 1988;Boatright etal., 1989;Nowak and 2;urawska, 1989 a). Dopamine and dopamine receptor agonists suppress the nocturnal increase of NAT activity and melatonin content of the retina, mimicking the effect of light.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation